2001
DOI: 10.1007/s10024001-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Nesidioblastosis and Mixed Hamartoma of the Liver in Beckwith-Wiedemann Syndrome: Case Study Including Analysis of H19 Methylation and Insulin-like Growth Factor 2 Genotyping and Imprinting

Abstract: An infant with persistent hyperinsulinemic hypoglycemia, diffuse nesidioblastosis, and mixed hamartoma of the liver (MHL), in addition to demonstrating clinical, pathologic, and molecular manifestations of Beckwith-Wiedemann syndrome (BWS), is the subject of this report. H19 methylation assay and allelic expression analysis for insulin-like growth factor 2 (IGF2) indicated that the patient was mosaic for paternal isodisomic cells and normal cells in lung tissue, nontumoral liver tissue, tissue from the MHL, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…This strengthens the idea based on observations in the liver that BWS favors not only embryonal malignant tumors but also, and less frequently, benign hamartomas [9] . In fact, neoplasms seem to occur in organs presenting malformative disturbances: the kidneys may present medullary dysplasia or persistent nephrogenesis and give rise to nephroblastoma.…”
Section: Discussionsupporting
confidence: 53%
“…This strengthens the idea based on observations in the liver that BWS favors not only embryonal malignant tumors but also, and less frequently, benign hamartomas [9] . In fact, neoplasms seem to occur in organs presenting malformative disturbances: the kidneys may present medullary dysplasia or persistent nephrogenesis and give rise to nephroblastoma.…”
Section: Discussionsupporting
confidence: 53%
“…In about 5% of children, the hyperinsulinemic hypoglycemia can be persistent and extend beyond the neonatal period, requiring either continuous feeding, medical therapy, or, in rare cases, partial pancreatectomy (17,18). In this group of children, the hypoglycemia can be severe, causing significant brain damage as well as death (19). The underlying mechanism(s) leading to persistent hyperinsulinemic hypoglycemia in this syndrome is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…IGF2 has also been reported with human overgrowth syndromes including Beckwith-Wiedeman syndrome, which has also been associated with nesidioblastosis. 13,[28][29][30] Studies in mice and transgenic mouse models has shown that the family of IGFs and IGF-binding proteins are involved in cellular functions including insulin and glucose regulation. 31 Direct evidence of the role of IGF2 and IGF-binding proteins on proliferation of insulinproducing cells has been reported in mice with disruption of the MEN1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] An association with Beckwith-Weideman syndrome has also been identified. 13,14 These genetic mutations have only rarely been identified in adult cases. 15,16 The lack of recognized mutations in most adult cases suggests that the pathogenesis of adult nesidioblastosis may be different from infantile nesidioblastosis.…”
mentioning
confidence: 99%